KAITAN ETNISITAS DENGAN KONFLIK SOSIAL DAN KEKERASAN MASSA DI TIGA DAERAH DI INDONESIA - Warsilah, Henny (P2KK LIPI, 2000)
This article is based on the field research of social conflicts in three areas in Indonesia (Tasikmalaya-West Java, Pekalongan-Central Java and Situbondo-East Java). In general it discusses the relationship between ethnicity (culture) and social conflict. The process of islamisation in the three areas has divided society into traditional moslem and the modernist. (In these conflicts, the state used a centralistic power to solve these conflicts, and transform it in quasi integrative). The centralistic attitude of new order government are supported by dual-function of ABRI and have resulted in the increasing state of social conflict.